Pendampingan Guru dalam Menggunakan Media Pembelajaran Berbasis Teknologi untuk Optimalisasi Pembelajaran - Arifin, Zainal; Surindra, Bayu; Irmayanti, Elis; Afandi, Tjetjep Yusuf; Lukiani, Eunike Rose Mita; Prastyaningtyas, Efa Wahyu (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
With the covid-19 pandemic, this makes learning different from usual, namely before the covid-19 pandemic learning was carried out face-to-face in school, but with the covid-19 pandemic as it is now finally learning is carried out remotely using the help of technology. Technological readiness both in terms of teachers as educators, the readiness of parents in providing facilities to students at home, and the readiness of students as implementers of distance learning must be prepared in advance so that learning can run smoothly. The purpose of community service activities is to assist teachers in using technology-based learning media for learning optimization. The steps used to overcome partner problems are: 1) program socialization; 2) training and practice in using technology-based learning media for learning optimization; 3) assistance; And 4) Monitoring. From the devotional activities that have been done, it is known that the enthusiasm of teachers in following ini mentoring shows high enthusiasm. This is evident from the strong willingness of teachers to be willing to understand and practice in creating modules using the Flip PDF application.